The Influence of Transformational Leadership on Employee Performance Through Organizational Citizenship Behavior (OCB) With Intensity Utilization of Social Media as a Moderating Variable (Study on MSMEs in Padang City) - Landra, Windra Agus; Rino, Rino (Human Resource Management Studies, 2023)
This study aims to examine and analyze the effect of: (1) transformational leadership on the performance of MSME employees in Padang City (2) transformational leadership on Organizational Citizenship Behavior of MSME employees in Padang City (3) Organizational Citizenship Behavior) on MSME employee performance in Padang City ( 4) transformational leadership on employee performance mediated by Organizational Citizenship Behavior of MSME employees in Padang City (5) the role of the intensity of using social media strengthens/weakens the effect of transformational leadership on Organizational Citizenship Behavior of MSME employees in Padang City. This research is a causal study with a population of 100 employees of micro, small and medium units in the city of Padang in the sub-districts of Padang Utara, Nanggalo, Koto Tangah and Pauh which work in micro, small and medium units of food and handicrafts. The sampling technique was taken using stratified random sampling and purposive sampling. Collecting data using a questionnaire with a Likert scale. The analysis technique used is SmartPLS 4 software. The results of data processing in this study indicate that: (1) Transformational leadership has a significant positive effect on the performance of MSME employees in Padang City (2) Transformational leadership has a significant positive effect on Organizational Citizenship Behavior (OCB) of MSME employees in Padang City (3) Organizational Citizenship Behavior (OCB) has a significant positive effect on the performance of MSME employees in Padang City (4) Transformational leadership has a significant positive effect on the performance of MSME employees in Padang City through Organizational Citizenship Behavior (OCB) (5) Intensity of media utilization social strengthens the relationship between transformational leadership has a significant effect on Organizational Citizenship Behavior.